STUDENTS’ DIFFICULTIES IN LISTENING COMPREHENSION - lina anisah; Laode Basri; Riskawati Riskawati (English Department, University of Riau Kepulauan, Batam,Indonesia, 2021)
Abstract This research was conducted to investigate students’ difficulties in listening comprehension and to find out the causes of students’ difficulties in listening comprehension. The design of this research was a case study. In conducting this research, the researcher took class XI IPA 4 of MAN 1 Kolaka as a subject of the research. To collect the data, the researcher used test, questionnaire and interview as instruments. Finally, based on the researcher’s investigation, the level of students’ difficulty in listening comprehension is classified into middle level, they were, student difficult to concentrate with noise sound (98%), to recognize the words the way they were pronounce (88%), to understand spoken text when speaker spoke too fast (83%), unclear sounds resulting from a poor-quality CD player (81%), to listen to English without transcription (80%), to understand well when the speaker spoke with a variety of accents (80%). Some causes of students’ difficulties in listening comprehension were noisy situations in class and environment, students could not match the sounds they heard with any script in their long-term memory, students limited short-term memory, text/passage was recorded while there were noises around or the cassette was used for such a long time, students have limited vocabulary, and unfamiliar accent. Keyword: Analysis, Difficulties in Listening Comprehension, Listening Comprehension.